Heroic hearts sentiment, saints, and authority in modern France - Popiel, Jennifer J. (University of Nebraska Press, 2021)
Heroic Hearts examines how young women in nineteenth-century France, authorized by a widespread cultural discourse that privileged individual authority over domesticity and marriage, sought to change the world.